Overuse in volleyball training/practice: A review on shoulder and spine-related injuries - Seminati, E.; Minetti, A. E. (European Journal of Sport Science, 2013)
Overuse injuries are predominant in sports involving the repetition of similar movements patterns, such as in volleyball or beach volleyball, and they may represent as much a problem as do acute injuries. This review discusses the prevalence of two of the most common overuse-related injuries in volleyball: shoulder and back/spine injuries. Risk factors and the aetiology of these injuries are illustrated in order to make possible to initiate preventive programme or post-injuries solutions. Data collected from literature showed a moderately higher injury rate for overuse shoulder injuries compared to the back/spine (19.0±11.2% and 16.8±9.7%, respectively). These data could be underestimated, and future epidemiological studies should consider overuse injuries separately from the others, with new methodological approaches. In addition to age, biomechanical and anatomical features of a volleyball technique utilised in game and the amount of hours played are considered as the main risk factors for overuse upper limb injuries, both for professional and recreational athletes. Together with post-injuries solutions, great importance has to be placed on preventive programmes, such as preventive rehabilitation, stretching, adequate warm up, strength-power exercises, etc. Furthermore, it is particularly suggested that coaches and players work together in order to develop new game/training techniques that minimise stresses and range of motion of the principal anatomical structures involved, while maintaining athletes performance.